The effect of tax harmonization law and tax sanctions on MSME taxpayer compliance in Jambi - Riski Hernando; Fitrini Mansur; Eko Prasetyo (Master in Accounting Program, Faculty of Business & Economics, Universitas Islam Indonesia, Yogyakarta, Indonesia, 2023)
This study examines the effect of the Tax Harmonization Law and Tax Sanctions on MSME Taxpayer Compliance in Jambi City. The research was conducted during the omicron variant of the covid-19 pandemic that hit in 2022. The study was tested on the MSME population in Jambi City with a sample of MSMEs in various sectors totaling 50 participants. Data were collected by distributed questionnaires and analyzed by Warp PLS 7.0. The results showed that the Tax Harmonization Law and Tax Sanctions had a significant positive effect on MSME Taxpayer Compliance in Jambi City. This research also contributes theoretically and practically and can be implemented for stakeholders and can be developed for further research.